Is Abu Yusuf’s Thought Still Relevant? A Qualitative Analysis Of The Digital Economy - Muhammad Yasin Mufti (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the relationship between Abu Yusuf's economic thinking and the current state of the digital economy. This research uses a qualitative approach with a case study method or qualitative case study research method to explore and describe the relationship between Abu Yusuf's economic thinking and the current state of the digital economy. The results indicate that Abu Yusuf created an autonomous economic system (not bound by government intervention). Its manifestation is seen in price settings that are contrary to the law of supply and demand. Apart from that, Abu Yusuf also gave several suggestions on ways to obtain long-term sources of expenditure, such as building bridges and dams and digging large and small canals. When talking about the provision of infrastructure facilities, Abu Yusuf stated that the state was responsible for fulfilling them in order to increase land productivity, people's prosperity and economic growth. He believes that all the costs required for procurement of public projects. Apart from the field of public finance, Abu Yusuf also gave his views on market mechanisms and prices. This is the same as the principle of the current digital economy where all transaction activities are carried out anywhere and at any time through an application on a device or other technology.